MARKERS OF VIOLENCE AGAINST OLDER ADULTS FROM THE NURSES' PERSPECTIVE - Santos-Rodrigues, Renata Clemente dos; Marcolino, Emanuella de Castro; Dantas, Ana Márcia Nóbrega; Barbosa, Lindemberg Arruda; Moraes, Ronei Marcos de; Souto, Rafaella Queiroga (Cogitare Enfermagem, 2024)
Objective: to identify the markers of violence against older adults from the nurses' perspective. Method: a qualitative study conducted between June and September 2021 in the state of Paraíba (Brazil), with the participation of nine nurses in two focus groups. The empirical material was transcribed in full and transformed into a text corpus with similarity analysis. Results: in the central core of the maximum tree, it was possible to observe terms common to more than one typification of violence, such as: “cycle of violence”, “trust”, “dominate”, “psychological distress”. In physical violence: “fractures”, “break” and “throw”; in psychological violence: “threat”, “fear”, “shame”, “injury”, “vaginal discharge” and “vaginal”; in financial violence: “withdrawal”, “dependence” and “take”; in neglect: “lack”, “supply” and “hygiene”; and in abandonment: “depression”, “loneliness” and “sadness”. Conclusion: this research values Nursing as a science and profession, especially in the forensic area, by investigating violence against older adults. The nurses' perception makes the Nursing Process more reliable and useful in identifying, reporting and solving incidents.